Exposure to Parental Smoking in Childhood is Associated with High C-Reactive Protein in Adulthood: The Cardiovascular Risk in Young Finns Study - Wang D; Juonala M; Viikari JSA; Wu F; Hutri-Kähönen N; Raitakari OT; Magnussen CG (My University, 2025)
Aim: Children exposed to parental smoking are at increased long-term risk of subclinical atherosclerosis in adulthood. However, it has not been quantified if exposure to parental smoking in childhood is associated with adult systemic inflammation. This study aimed to determine if childhood exposure to parental smoking was associated with high-sensitivity C-reactive protein (hsCRP) in adulthood.
Methods: This longitudinal analysis of 2,511 participants used data from the Cardiovascular Risk in Young Finns Study, a prospective cohort of Finnish children. In 1980 or 1983, parents self-reported their smoking status and serum hsCRP was collected up to 31 years later in adulthood.
Results: Compared with children with non-smoking parents, the relative risk of developing high hsCRP (＞3 mg/L) in adulthood increased among those with 1 or both parents who smoked [relative risk (RR), 1.3; 95%confidence interval (CI), 1.0-1.8] after adjustment for socioeconomic status, cardiovascular risk factors, and smoking status in childhood and adulthood. Moreover, children exposed to mother smoking [RR, 2.4; 95% CI, 1.3-4.2] had highest risk of developing high hsCRP in adulthood compared with those exposed to father smoking [RR, 1.6; 95% CI, 1.2-2.3] and both parents smoking [RR, 1.4; 95% CI, 0.9-2.0].
Conclusion: Our findings suggest that children exposed to parental smoking are at increased risk of having high hsCRP in adulthood. Limiting children's exposure to passive smoking may have long-term benefits on general low-grade inflammation.